Care in psychiatric hospital under the perspective of a nursing team - Claudia Mara de Melo Tavares; Elaine Antunes Cortez; Marcela Pimenta Muniz (Rev Rene)
The present study is aimed at describing the perception of the nursing team concerning the care in a psychiatric hospital. The research used a qualitative approach, exploratory type, using focus group technique, with five participants, in August 2011, in Niteroi, RJ, Brazil. From the data analysis five categories emerged, covering: sensitive listening; personal availability; therapeutic projects; human issues of the team; Traditional Psychiatry vs. Psychosocial Paradigm tension. It was concluded that despite the research, the subjects were still working at the hospital model. It was possible to bring awareness in a human, comprehensive and complete manner. But this perception of care has frailties once it does not bring any evidence of scientific basis of nursing. It is recommended that the professional nursing team invest in their role of caring in the context of the Psychiatric Reform, in the pursuit of an approach centered on the subject and in his way of living.